Non-sustained ventricular arrhythmias at exercise ECG predict severe ventricular arrhythmias in arrhythmic mitral valve prolapse. (3rd October 2022) - Five, C K; Hasselberg, N E; Chivulescu, M; Rootwelt-Norberg, C; Ribe, M P; Dejgaard, L; Castrini, A I; Aabel, E W; Haugaa, K H
Abstract: Background: A subset of patients with mitral valve prolapse experience ventricular arrhythmias (VA) and even sudden cardiac death, defined as arrhythmic mitral valve prolapse (AMVP). Risk stratification of VA is challenging in this relatively young population. The predictive role of exercise testing has not been investigated. Purpose: We aimed to explore if VA burden on exercise ECG can predict severe ventricular arrhythmic events in AMVP patients. Methods: We included consecutive AMVP patients without prior severe VA referred to our tertiary center. Exercise bicycle ECG test by standard protocol was performed at inclusion. Non-sustained VT (nsVT) during exercise testing was defined as ≥3 consecutive ventricular beats with a rate ≥100/min lasting <30 seconds. Our endpoint of severe VA during follow-up was defined as aborted cardiac arrest, sustained ventricular tachycardia, nsVT with syncope or appropriate ICD shock therapy detected by either ECG, Holter monitoring, implantable loop recorder or primary preventive ICD. Results: We included 91 AMVP patients without prior severe VA (51±16 years of age, 63% women) with exercise test at baseline. NsVT occurred in 5 patients during exercise testing. During 67±7 months of follow-up, 5 (5.5%) patients experienced severe VA. In all, 3 of the 5 (60%) with nsVT at exercise test experienced severe VA during follow-up, compared to only 2 of 86 (2%) without nsVT at exercise testing (age adjusted hazard ratio [HR] 35 [95% CI 5–249], p<0.001). Survival free from severe VA was worse in those with nsVT at exercise test (log rank p<0.001) (Figure 1). Conclusions: Non-sustained VT occurring during exercise ECG testing was a strong marker of subsequent severe VA in AMVP patients without previous severe VA. These novel findings indicate that exercise testing may improve risk stratification in AMVP patients. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): The Research Council of Norway.